Dependence of metal surface properties on the valence-electron density in the stabilized jellium model - Brajczewska, Marta (2001)
The stabilized jellium model is the simplest model which yields realistic results for the physical properties of simple metals. For the surface properties, its single input is the valence-electron density, which is described by the density parameter rs. We remark that the surface energy and the work function as a function of rs, within that model, are reasonably approximated by power laws and compare that behaviour with similar descriptions found in the literature and with experiment. We also present a simple relationship between the surface energy and the bulk modulus, which is well fitted by the power of the density parameter (when the effective valence is taken to be z*=1). Another simple relationship between the work function and the bulk modulus is shown.